An Evaluation of Tahfidz Al-Quran Program at Mahir Bil Quran Junior High School Semper, Cilincing, North Jakarta District - Yayat Suharyat; Ibnu Muthi; Novi Eko Hadiyanto (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
This study aims to describe the evaluation of the Tahfidz Program at Tahfidz Mahir Bil Qur'an Junior High School Cilincing, North Jakarta. The evaluation components focus on the context, input, process, and product of the Tahfidz Program. This type of research is Evaluative Research. The evaluation model used in this study is the CIPP evaluation model. Data collection techniques using IOD (Interview, Observation, and Documentation). The research results are as follows: 1) From the context component, the formulation of the vision, mission, and objectives of the tahfidz program needs to reorganize. The vision, mission, and aim need to be improved and adjusted. Some criteria are still out of sync, and there has been no evaluation of changes since 2015 until now. 2) The input component shows that the teacher's input has been stated well. As for student input, it is necessary to note that the criteria for acceptance of students to Advanced Junior High School need to be emphasized because this will affect the target of achieving tahfidz itself. Curriculum inputs indicate that there is a need for standard and documented curriculum reforms. The input of facilities and facilities, in general, is good, it's just that for the 4th floor it needs to be reviewed because it still feels uncomfortable. 3) From the components of the process, the use of methods, materials, and time are good. It's just that maximizing existing resources does not feel optimal. 4) From the components of the product, it's still not good. Many of the targets have been missed the target. A program can be continued by decreasing of memorization target.